Improvement proposal for the control and management of a warehouse with stationery products - Villamil, Citlali (2024)
Inventory management is essential for balancing stock levels, reducing costs, and preventing order delays by identifying high-demand products. This work focused on developing a comprehensive inventory system for the warehouse of a stationery company, enhancing product control using the ABC technique. The research, descriptive in nature, analyzed the characteristics of the inventory system in the stationery store and proposed areas for improvement. A hierarchical classification of products was implemented, allowing for more accurate management in purchasing, forecasting, and reordering policies, minimizing the risks of obsolescence and waste in low-turnover products. The applied method facilitated strategic decision-making by providing a clear view of the inventory structure and optimizing operational efficiency to meet customer demands.